Analisis dan Faktor Indeks Pembangunan Manusia di Jawa Tengah - Aan Riana; Muhammad Khafid; Shanty Oktavilia (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2022)
Human development is a concept used to improve the quality of people's lives and to achieve the common goals of a country. This study aims to determine the effect of Poverty, Growth Rate and Minimum Wage on the Human Development Index in Central Java. This type of research is quantitative research. This study uses panel data with a total of 175 observations consisting of time series data for 2016-2020 and cross data of 35 districts/cities in Central Java Province. The results of this study indicate that there is a significant effect of poverty, growth rate and minimum wage on the Human Development Index. Poverty has a significant negative effect on the Human Development Index, the growth rate has a positive and significant effect on the Human Development Index and the minimum wage has a positive and significant effect on the Human Development Index.